Associations between the MDM2 promoter P1 polymorphism del1518 (rs3730485) and incidence of cancer of the breast, lung, colon and prostate - Gansmo, Liv B. (Oncotarget, 2016)
The MDM2 promoter region contains several polymorphisms, some of which have been associated with MDM2 expression, cancer risk and age at cancer onset. del1518 (rs3730485) is an indel polymorphism residing in the MDM2 promoter P1 and is in almost complete linkage disequilibrium with the MDM2 promoter P2 polymorphism SNP309T>G (rs2279744). Cancer risk assessments of del1518 have previously been conducted in relatively small Chinese populations only. In this study we assessed the genotype distribution of del1518 among healthy Caucasians, African Americans and Chinese, and we estimated the Odds Ratios (OR) for incident cancer of the breast, colon, lung and prostate (n=7,081) as compared to controls (n=3,749) in a large Caucasian (Norwegian) cohort. We found the genotypes of the del1518 to vary significantly between healthy Caucasians, African-Americans and Chinese (p< 1×10(−5)). Further, we found a positive association of the del1518 del-allele with risk of colon cancer (dominant model: OR = 1.15; 95 % CI = 1.01 – 1.31). Stratifying according to SNP309 status, this association remained among carriers of the SNP309TG genotype (OR = 1.21; 95 % CI = 1.01 – 1.46), but with no clear association among carriers of the SNP309TT genotype. In conclusion, our findings suggest del1518 to be associated with increased risk of colon cancer.